Proposing a New Classification for Managing Prostaglandin-Induced Enophthalmos in Glaucoma Patients - Ferraro V; Gaeta A; Barone G; Confalonieri F; Tredici C; Vinciguerra P; Di Maria A (Clinical Ophthalmology)
Vanessa Ferraro,1 Alessandro Gaeta,2 Gianmaria Barone,3 Filippo Confalonieri,4 Costanza Tredici,4 Paolo Vinciguerra,3,4 Alessandra Di Maria4 1Department of Ophthalmology, Humanitas San Pio X, Milan, Italy; 2Department of Internal Medicine and Medical Specialties (DIMI), Università Di Genova, Genova, Italy; 3Department of Biomedical Sciences, Humanitas University, Pieve Emanuele, Milan, Italy; 4Department of Ophthalmology, IRCCS Humanitas Research Hospital, Rozzano, Milan, ItalyCorrespondence: Alessandra Di Maria, Humanitas Research Hospital, Via Alessandro Manzoni, 56, Rozzano, Milan, 20089, Italy, Email info@alessandradimaria.itPurpose: Glaucoma is commonly treated with prostaglandin analogs (PGAs), which effectively reduce intraocular pressure. However, PGAs can cause ocular side effects, including prostaglandin-associated periorbitopathy syndrome (PAPS), characterized by fat loss, enophthalmos and increased orbital structure prominence. The underlying mechanism is believed to involve adipocyte apoptosis, altered lipid metabolism, and changes in soft tissue dynamics. Currently, there is no standardized grading for enophthalmos, complicating its management. This study aimed to classify prostaglandin-induced enophthalmos and explore surgical or minimally invasive treatments, focusing on Italian Caucasian patients.Materials and Methods: The study, conducted at IRCCS Humanitas Research Hospital between 2005 and 2023, assessed PAPS in primary open-angle glaucoma patients. It included a two-phase approach: (1) classification of enophthalmos using clinical and radiological measures to create a composite PAPS score; and (2) evaluation of treatment options, including Calcium Hydroxylapatite (CAHY) injections and autologous fat grafting.Results: A retrospective analysis of 120 glaucoma patients with prostaglandin-induced enophthalmos identified severity levels using the PAPS classification. The proposed therapeutic algorithm stratifies treatment: mild cases benefit from conservative management or fillers, moderate cases from calcium hydroxyapatite (CAHY) injections, and severe cases from combined CAHY and autologous fat grafting.Conclusion: A lack of a standardized grading system hinders consensus on management of PAPS. We propose a novel composite scoring system integrating six clinical parameters to stratify patients and tailor a minimally invasive therapeutic approach using calcium hydroxyapatite fillers and autologous fat grafting to restore orbital volume, improve eyelid aesthetics, and reduce complications. This classification system may serve as a clinical tool in patients with persistent or advanced PAPS who seek cosmetic correction or relief from functional symptoms.Keywords: prostaglandin-associated periorbitopathy syndrome, prostaglandin-induced enophthalmos, calcium hydroxyapatite, autologous fat grafting, glaucoma therapy complications, classification system, enophtalmos, orbital changes in glaucoma